A virtual test platform for railway draft gear designs. (6th September 2021) - Wu, Qing; Cole, Colin; Spiryagin, Maksym; Ma, Weihua; Luo, Shihui
Draft gear design and assessment processes commonly use results from physical drop-hammer tests, vehicle impact tests and laboratory rig tests which all utilise quite different impact velocity ranges and impact severities. Due to the velocity dependent characteristic of friction and viscous damping, draft gears can better be designed and assessed by using comprehensive draft gear test simulations. This paper developed a multipurpose virtual test platform for draft gear designs; the virtual platform can conduct drop-hammer test simulations, vehicle impact test simulations and laboratory rig test simulations for different types of draft gears using different published draft gear models. The development for the virtual platform has used a versatile draft gear model that can simulate a number of different draft gear designs by using one model template; it has also used a multipurpose simulation strategy that can simulate different draft gear tests using the same dynamics model.